Clinical Trials with Pegylated Liposomal Doxorubicin in the Treatment of Ovarian Cancer. (14th March 2013) - Pisano, Carmela; Cecere, Sabrina Chiara; Di Napoli, Marilena; Cavaliere, Carla; Tambaro, Rosa; Facchini, Gaetano; Scaffa, Cono; Losito, Simona; Pizzolorusso, Antonio; Pignata, Sandro
Abstract : Among the pharmaceutical options available for treatment of ovarian cancer, increasing attention has been progressively focused on pegylated liposomal doxorubicin (PLD), whose unique formulation prolongs the persistence of the drug in the circulation and potentiates intratumor accumulation. Pegylated liposomal doxorubicin (PLD) has become a major component in the routine management of epithelial ovarian cancer. In 1999 it was first approved for platinum-refractory ovarian cancer and then received full approval for platinum-sensitive recurrent disease in 2005. PLD remains an important therapeutic tool in the management of recurrent ovarian cancer in 2012. Recent interest in PLD/carboplatin combination therapy has been the object of phase III trials in platinum-sensitive and chemonaïve ovarian cancer patients reporting response rates, progressive-free survival, and overall survival similar to other platinum-based combinations, but with a more favorable toxicity profile and convenient dosing schedule. This paper summarizes data clarifying the role of pegylated liposomal doxorubicin (PLD) in ovarian cancer, as well as researches focusing on adding novel targeted drugs to this cytotoxic agent.